add two square - 5 x square y square + 2
X Y and 6 X Y + 4 x square - 7 and
subtract the results from minus x y + x
square + 7 x square y square
Answers
Answered by
2
Answer:
5x²y² - 9xy - 3x² + 7x + 7 (ans)
Step-by-step explanation:
= -5x²y²+2xy + 6xy+4x²-7
= -5x²y² + 2xy + 6xy + 4x² - 7
= -5x²y² + 8xy + 4x² - 7
substract:-
= -xy + x² + 7x - (-5x²y² + 8xy + 4x² - 7)
= -xy + x² + 7x + 5x²y² -8xy - 4x² + 7
= 5x²y² - xy - 8xy + x² - 4x² + 7x + 7
= 5x²y² - 9xy - 3x² + 7x + 7 (ans)
Similar questions